Alternaria alternata (Fr) Keissl Crude Extract Inhibits HIV Subtypes and Integrase Drug-Resistant Strains at Different Stages of HIV Replication - Darian Naidu; Ernest Oduro-Kwateng; Mahmoud E. S. Soliman; Sizwe I. Ndlovu; Nompumelelo P. Mkhwanazi (Pharmaceuticals)
Background/Objectives: The development of HIV drug resistance to current antiretrovirals, and the antiretrovirals’ inability to cure HIV, provides the need of developing novel drugs that inhibit HIV-1 subtypes and drug-resistance strains. Fungal endophytes, including Alternaria alternata, stand out for their potentially antiviral secondary metabolites. Hence, this study investigates the anti-HIV activities and mechanism of action of the A. alternata crude extract against different HIV-1 subtypes and integrase-resistant mutant strains. Methods: Cytotoxicity of the A. alternata crude extract on TZM-bl cells using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay was performed. The crude extract antiviral activity against subtypes A, B, C, and D and integrase drug-resistant strain T66K and S230R was determined using a luciferase-based antiviral assay. Luciferase and p24 ELISA-based time-of-addition assays were used to determine the mechanism of action of the crude extract. Docking scores and protein ligand interactions of integrase T66K and S230R strains against the identified bioactive compounds were determined. Results: The crude extract CC50 was 300 μg/mL and not cytotoxic to the TZM-bl cell lines. In HIV-1 subtypes A, B, C, and D, the crude extract exhibited 100% inhibition and therapeutic potential. The A. alternata crude extract had strong anti-HIV-1 activity against integrase strand transfer drug-resistant strains T66K and S230R, with a 0.7265- and 0. 8751-fold increase in susceptibility. The crude extract had antiviral activity during attachment, reverse transcription, integration, and proteolysis. In silico calculations showed compounds 2,3-2H-Benzofuran-2-one, 3,3,4,6-tetramethyl-, 3-Methyl-1,4-diazabicyclo[4.3.0]nonan-2,5-dione, N-acetyl, Coumarin, 3,4-dihydro-4,5,7-trimethyl-, Cyclopropanecarboxamide, N-cycloheptyl, Pyrrolo[1,2-a]pyrazine-1,4-dione, and hexahydro-3-(2-methylpropyl)- crude extract bioactive compounds had strong docking scores and diverse binding mechanisms with integrase. Conclusions: The A. alternata crude extract demonstrates strong antiviral activity against different HIV-1 subtypes and integrase drug-resistance strains. The extract inhibited various stages of the HIV-1 life cycle. The bioactive compounds 2,3-2H-Benzofuran-2-one, 3,3,4,6-tetramethyl-, 3-Methyl-1,4-diazabicyclo[4.3.0]nonan-2,5-dione, N-acetyl, Coumarin, 3,4-dihydro-4,5,7-trimethyl-, Cyclopropanecarboxamide, N-cycloheptyl, Pyrrolo[1,2-a]pyrazine-1,4-dione, and hexahydro-3-(2-methylpropyl)- may be responsible for the antiviral activity of A. alternata.